Within-day and between-day repeatability of shank-mounted inertial measurement unit in gait analysis - Lavonen, Juho (2025)
Lavonen, J. 2025. Within-day and between-day repeatability of shank-mounted inertial measurement unit in gait analysis. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis in biomechanics, 52 pp.